Compositionally Tunable Photoluminescence Emission in Cu2ZnSn(S1−xSex)4 Nanocrystals1. Issue 35 (18th June 2013) - Singh, Ajay; Singh, Shalini; Levcenko, Sergiu; Unold, Thomas; Laffir, Fathima; Ryan, Kevin M.
<x xml:space="preserve">Abstract</x> Inorganic nanostructures: Alloyed Cu2ZnSn(S1−xSex)4 wurtzite nanocrystals (10 nm in size) with a varying composition (x=0–1) were synthesized using a colloidal hot injection route. A photoluminescence (PL) emission study of these nanocrystals shows a compositionally tunable band‐gap ranging between 0.9–1.4 eV that directly correlates to the sulfur‐to‐selenium ratio (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>